Acinar Cell Carcinoma of the Pancreas Associated with Subcutaneous Panniculitis - Moro, Margherita; Moletta, Lucia; Blandamura, Stella; Sperti, Cosimo (JOP. Journal of the Pancreas, 2011)
Context Acinar cell carcinoma is a rare pancreatic malignant tumor, which can be associated with a particular manifestation: pancreatic panniculitis. It presents with erythematous subcutaneous nodules located mainly on the legs. The skin lesions can precede, be concurrent with or follow the pancreatic illness. The pathogenesis is not fully understood, but it is believed to be associated with high levels of serum lipase produced by the neoplasm, causing fat necrosis in tissues. The treatment of pancreatic panniculitis is directed at the underlying pancreatic disease, which may result in regression of the skin lesions. We report a case of pancreatic acinar cell carcinoma associated with subcutaneous panniculitis together with a review of the English literature. Case report A 79-year-old woman, with a 13-month history of acute pancreatitis, asthenia, weight loss, and the CT finding of a mass in the pancreatic head, presented complaining of multiple, migrant and painful subcutaneous nodules on her lower extremities. High serum lipase levels were also present. She underwent a pancreaticoduodenectomy, with subsequent regression of the skin lesions and normalization of her serum lipase levels. Histology revealed an acinar cell carcinoma of the pancreas. Liver metastases occurred six months after surgery, and the patient underwent chemotherapy with gemcitabine. She is still alive 14 months after the initial surgery. Conclusions Although rare, the association between acinar cell carcinoma and pancreatic panniculitis has been described in the literature. In a patient with subcutaneous nodules, the presence of acinar cell carcinoma should be considered in order to prevent long delays in the diagnosis and treatment of this pancreatic malignancy. Image: Multiple erythematous subcutaneous nodules on the lower legs.